Diagnostic Role of Ultrasonography in Right Iliac Fossa Pathologies - Javaid, Mishal; Tariq, Ayesha; Javaid, Hiba Noreen (International Journal of Applied Sciences and Biotechnology, 2019)
Ultrasound is often the imaging modality of choice in patients with acute right iliac fossa pain. Right iliac fossa pain remains the commonest clinical dilemma encountered by general surgeons. The management of acute right iliac fossa pain is audited, examining the relationship between symptom duration, use of pre-operative radiological imaging and patient outcome. Objective: To determine the diagnostic role of ultrasonography in Right Iliac Fossa pathologies. Methods: A cross sectional descriptive study was carried out at the Department of Radiology in Sir Ganga Ram Hospital Lahore, Pakistan. Duration of study was from March 2018 to November 2018. 85 patients with Right Iliac Fossa pain selected through convenient sampling technique. Statistical software for social sciences (SPSS version 22.0) is used for the analysis of data. Conclusion: The results in the study reflect findings from high volume emergency surgical departments and patients of pain in right iliac fossa demonstrating that unfocussed abdominal and pelvic ultrasounds are not an appropriate use of resources in patients with Right iliac fossa pain. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 382-386